(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The ability to maintain employees in a gig depends on a balance between fun and serious activities, which is a creating region in human assets on the board. Workers, especially women, take a terrible risk by juggling family responsibilities and work obligations. Administration in the fields of education, banking, security, and emergency medical care are especially needed in this context and in the more rural areas as well. In light of this context, the aim of this review was to attempt to put a number on the amount of time female aid workers spend on both leisure and work-related pursuits in various parts of the Coimbatore District. The analyst has successfully recruited fifty women for positions in education, healthcare, banking, and security. The data was gathered using a structured survey as a template, and then analyzed using statistical tools like the rate and Chi-square. Based on the findings, it appears that the majorities of female employees across all support sectors are highly fulfilled in their personal lives and have a moderate level of satisfaction at work.